Is Outpatient Anterior Lumbar Fusion (ALIF) Safe? An Analysis of 30-day Outcomes. Issue 4 (10th May 2023) - Jones, Jeremy; Malik, Azeem Tariq; Khan, Safdar N.; Yu, Elizabeth; Kim, Jeffery
Abstract : Study Design: Review of publicly available database. Objective: To compare 30-day outcomes of single-level ALIF procedures performed in outpatient and inpatient settings. Summary of Background Data: Despite a growing interest in performing standalone anterior lumbar interbody fusions (ALIFs) as an outpatient procedure, no study has evaluated the safety or efficacy of this procedure outside an inpatient setting. Methods: The 2012–2017 American College of Surgeons-National Surgical Quality Improvement Program (ACS-NSQIP) was queried using CPT code 22558 to identify patients undergoing a single-level ALIF. Patients receiving concurrent posterior lumbar surgery/fusion/instrumentation, pelvic fixation, or surgery due to tumor, trauma and/or deformity were excluded to capture an isolated cohort of patients receiving single-level standalone ALIFs. A total of 3728 single-level standalone ALIFs were included in the study. Multivariate regression analyses were used to compare 30-day adverse events and readmissions while controlling for baseline clinical characteristics. Results: Out of a total of 3728 ALIFs, 149 (4.0%) were performed as outpatient procedure. Following adjustment, outpatient ALIFs versus inpatient ALIFs had lower odds of experiencing any 30-day adverse event (2.0% vs. 9.2%, OR 0.24 [95% CI 0.08–0.76]; P =0.015). No significant differences were noted with regard to severe adverse events 9p=0.261), minor adverse events 9p=0.995), and readmission rates ( P =0.95). Conclusion: On the basis of the results of the study, it appears that ALIFs may be carried out safely in an outpatient setting in an appropriately selected patient population.